English against Englishing: The Case of an Early English Translation of an Oriya Novel - Mohapatra, Himansu (TTR, 2010)
Successive translations of a text mirror the shifting translatory practices of a culture. Paradigms for/of translation can be tracked by following the trajectory of these translations. Usually, however, the “translative turn” is read off from the latest in the series of translations inspired by a text. It is the other way round with the translated Oriya novel, Fakir Mohan Senapati’s Chhamana Athaguntha (1902), which is an exception to this developmentalist rule. An early English translation of the novel titled The Stubble under the Cloven Hoof (1967), produced by C.V.N. Das, shows a highly visible and active translator. In this Das uses English to counter the Englishing tendencies that are the inevitable end result of his attempt, as he says, at “rechristening” a vernacular tale. This essay demonstrates this and also explains the related phenomenon of the foregrounding of the task of the translator.